Management of liver trauma by laparoscopy using infrahepatic inferior vena cava partial clamping: A case report - Zhang, Dan; Tan, Ming-Da; Zheng, Ming-You; Wang, Huai-Zhi; Xiao, Lin-Kang (Frontiers in Surgery, 2023)
Liver trauma with hemodynamic instability is extremely dangerous. Exploratory surgery after fluid resuscitation is a potentially effective method to save lives. Although great advances in laparoscopic technique for hepatectomy, laparoscopy is rarely used for liver trauma. According to our previous experience, laparoscopic infrahepatic inferior vena cava (IVC) clamping was a safety and effective technique to reduce central venous pressure (CVP) and control bleeding during hepatectomy. In this article, we described a case of grade Ⅴ liver trauma that had been managed by totally laparoscopic approach using infrahepatic IVC partial clamping, providing a safely alternative option for selected liver trauma patients.